Antimycotic Inhibition of Phytophthora colocasiae (Taro Leaf Blight) Using Diverse Disease Management Paradigms - Mjaika, Ndifon Elias (Talenta Publisher, 2023)
Cocoyam/taro production has been plagued with many constraints, especially taro leaf blight. This study aimed at providing useful control options for the management of taro leaf blight. Two in vitro sub-trials (using botanicals alone or chemicals+botanicals) were conducted. A completely randomized design with each treatment replicated thrice was used and analyzed at a 95% confidence level. P. colocasiae was effectively inhibited by Balsam, Thyme, Lantana, Eucalyptus, and Alligator-pepper up to 144 Hours After Inoculation (HAI) with a 144-HAI-moving average of 69.5%. At 48, 96, and 144 HAI, Eucalyptus 100% concentration, Thyme (50 and 100%), Lantana 100%, and Alligator-pepper (50 and 100%) were excellent control resources. Percentage inhibition of the pathogen by plant extracts ranged from 13.8-100%. Combinations of Mancozeb and MetCop (i.e. Metalaxyl+Copper(I)oxide) with botanicals (Balsam, Lantana, and Thyme) controlled P. colocasiae. Inhibition of radial growth of P. colocasiae ranged from 0-100% with a 168-HAI-moving average of 55.5%. Combining Thyme with Mancozeb or MetCop significantly inhibited P. colocasiae more compared to other treatments. Mancozeb+Balsam 50% and MetCop+Balsam 100%, followed by Mancozeb+Lantana 100%, MetCop+Lantana 100%, and Mancozeb+Balsam 100% were the best treatments. Mancozeb was better than MetCop. Chemical rates can be reduced by using botanicals since chemicals affect health.